2010
DOI: 10.1002/jcop.20413
|View full text |Cite
|
Sign up to set email alerts
|

School engagement, risky peers, and student–teacher relationships as mediators of school violence in Taiwanese vocational versus academically oriented high schools

Abstract: Educational tracking based on academic ability accounts for different school dynamics between vocational versus academically-oriented high schools in Taiwan. Many educational practitioners predict that the settings of vocational schools and academic schools mediate school violence in different ways. Alternatively, some researchers argue the actual mediating mechanism may not vary significantly between the different school types in different cultures. The purpose of this study was to examine how within-school v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Teachers have a great influence on the classroom climate and serve as role models for children. Studies of Taiwanese adolescents showed that student-teacher relationships and abusive practices by teachers contribute to students' aggressive behavior and delinquency (Chen and Astor 2011;Wei et al 2010). School administrators, therefore, may need to pay special attention to victimization of students by teachers, since it not only causes direct psychological impact but may also stimulate peer aggression.…”
Section: Discussionmentioning
confidence: 97%
“…Teachers have a great influence on the classroom climate and serve as role models for children. Studies of Taiwanese adolescents showed that student-teacher relationships and abusive practices by teachers contribute to students' aggressive behavior and delinquency (Chen and Astor 2011;Wei et al 2010). School administrators, therefore, may need to pay special attention to victimization of students by teachers, since it not only causes direct psychological impact but may also stimulate peer aggression.…”
Section: Discussionmentioning
confidence: 97%
“…Chen & Astor 2011;Finn & Zimmer 2012;Kuh 2009;Salmela-Aro et al 2008). In studies with University students, engagement has been measured primarily with the UWES-SS in Europe and the BCSSE in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…The growing body of research, primarily conducted in the United States and Australia, shows that student engagement can act as an antidote to low academic achievement, student burnout, student lack of resilience, dissatisfaction, and school dropout (Christenson & Reschly 2010;Elmore & Huebner 2010;Finn & Zimmer 2012;Wang & Eccles 2012;Krause & Coates 2008). It can also act as a strong mediator between out-of-school variables (e.g., home and family, friends and class-inmates,) (Chen & Astor 2011), teacher-student interactions, academic achievement, school success and life-long learning Gilardi & Guglielmetti 2011;. Recent studies have found a correlation between different engagement profiles and students' learning (Wang & Eccles 2012) and physical and psychological health and well-being (Li & Lerner 2011;Wang & Eccles 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, frequent victimisation by peers at school is associated with poor academic performance (Schwartz, Gorman, Nakamoto, & Toblin, 2005). Violence perpetrated in and around school, including on the Internet, is interpreted as a threat to safety and social cohesion (Chen & Astor, 2011;Finkelhor, Omrod, Turner, & Hamby, 2011;Siu, 2011). Violence-related experiences in and around schools are therefore a major concern in the educational policy of countries such as the United States relationship patterns between personal and other characteristics of secondary school pupils and their motives as a victim, perpetrator, or witness of six types of violent behaviour, in relation to the complementary social roles of other pupils, teachers, other school staff, and pupils' relatives.…”
mentioning
confidence: 99%